A comparative study of anion-exchange membranes tethered with different hetero-cycloaliphatic quaternary ammonium hydroxides. Issue 41 (13th October 2017) - Dang, Hai-Son; Jannasch, Patric
Abstract : Quaternary ammonium (QA) cations with high alkaline stability are crucial for the long term performance of anion-exchange membrane (AEM) fuel cells. Abstract : Quaternary ammonium (QA) cations with high alkaline stability are crucial for the long term performance of anion-exchange membrane (AEM) fuel cells. Here, we have tethered poly(phenylene oxide) (PPO) with 8 different hetero-cycloaliphatic QA cations via pentyl spacer chains. The thermal and alkaline stabilities, as well as hydroxide ion conductivity, were systematically evaluated with the primary aim to identify degradation reactions and establish cation design principles. The study included AEMs functionalized with 1-methylazepanium, 1-methylpyrrolidinium, 1-methylmorpholinium, quinuclidinium, as well as 1-methyl-, 1, 4-dimethyl-, 1, 3, 5-trimethyl-, and 1, 2, 6-trimethylpiperidinium, all within a narrow ion exchange capacity (IEC) range. For reference, PPO was also functionalized with trimethylammonium and dipropylmethylammonium cations on pentyl spacers, and with trimethylammonium and 1-methylpiperidinium QAs in benzylic positions directly on the PPO backbone. The alkaline stability of hetero-cycloaliphatic QA cations was found to depend critically on their position in the polymer structure, ring size, the presence of an additional heteroatom and ring substitution pattern. For example, 1, 2, 6-trimethylpiperidinium and 1-methylazepanium degraded via Hofmann elimination and 1-methylmorpholinium via ring opening by both Hofmann elimination and substitution reactions, while no degradation was detected by 1 H NMR spectroscopy of other cations after 16 days in 1 M NaOH at 90 °C. The hydroxide ion conductivity of the AEMs in the study reached values between 64 and 150 mS cm −1 at 80 °C, depending on the cation and IEC. AEMs tethered with piperidinium and quinuclidinium cations via pentyl spacers were found to show the best overall properties. Hence, the combined results provide insights that may guide the selection of cationic groups and membrane materials to improve the durability and performance of alkaline electrochemical energy conversion and storage devices.